Single-incision laparoscopic cholecystectomy versus conventional multi-port laparoscopic cholecystectomy: A systematic review, meta-analysis, and meta-regression of randomized controlled trials [version 2; peer review: 1 approved, 2 approved with reservations] - Ricarhdo Valentino Hanafi; Reno Rudiman; Alma Wijaya (F1000Research, 2024)
Background Conventional multi-port laparoscopic cholecystectomy (CMLC) has become the current ‘gold standard’ technique in gallbladder disease. Single-incision laparoscopic cholecystectomy (SILC) has gained attention due to its benefits in improving patient cosmetic results and pain reduction. We aim to assess the latest evidence on the feasibility, safety and surgical outcomes of SILC and CMLC. Methods We conducted searches for randomized controlled trials (RCTs) in PubMed, PubMed Central (PMC), and Europe PMC between December 2011 and 2021. The latest search was conducted in January 2022. We analyzed several outcomes, including perioperative complications, estimated blood loss, operation time, conversion to open surgery, hospital stay, pain score, cosmesis, and days of return to work. Cochrane Risk of Bias (RoB) 2.0 tool was used to evaluate quality of studies. Mantel-Haenszel’s formula and Inverse Variance method were conducted to synthesize results. This study was accomplished in accordance with the PRISMA guidelines. Results A total of 37 studies were eligible, with a total of 2,129 and 2,392 patients who underwent SILC and CMLC. Our study demonstrated a superiority of SILC for the visual analog score (VAS) at six hours post-operation [mean difference (MD) -0.58 (95% CI -1.11, -0.05), p=0.03], cosmesis one-month post-operation [standard MD 2.12 (95% CI 1.10, 3.13), p<0.0001], and cosmesis six months post-operation [standard MD 0.53 (95% CI 0.06, 0.99), p<0.0001]. Meanwhile, SILC showed a longer operation time [MD 10.45 (95% CI 6.74, 14.17), p<0.00001]. In terms of VAS at four time points (4, 8, 12, and 24 hours), perioperative complications, estimated blood loss, conversion to open surgery, hospital stay and days to return to work, SILC did not differ from CMLC. Conclusions SILC is a safe, feasible and favorable procedure in terms of pain reduction and cosmetic results. The option between both procedures is based on surgeon preferences. Registration: PROSPERO (CRD42022306532; 23 February 2022).